2021
DOI: 10.1097/gme.0000000000001724
|View full text |Cite
|
Sign up to set email alerts
|

The short-term effects of estradiol, raloxifene, and a phytoestrogen in women with perimenopausal depression

Abstract: Objective: We examined the short-term efficacies of three estrogen-like compounds under placebo-controlled conditions in women with perimenopause-related depression (PMD). Methods: Women with PMD were randomized in a double-blind parallel design to one of four treatments: transdermal 17-beta estradiol (TE) (100 mcg/d); oral raloxifene (60 mg/d); a proprietary phytoestrogen compound, Rimostil (1,000 mg twice/d); or placebo for 8 weeks. The main outcome m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 94 publications
0
23
0
1
Order By: Relevance
“…Embora seja usado como suplemento alimentar nesse país, nunca obteve aprovação para uso médico. Schmidt et al (2021) desenvolveram um estudo clínico randomizado para avaliar o efeito sobre a depressão de mulheres no período da menopausa, onde utilizaram 4 grupos: palacebo; estradiol; raloxifene (fitohormônio da classe das benzofenonas) e o suplemento rimostil (isolflavonas isoladas de Trevo vermelho). Neste estudo para avaliar a ação desses produtos na redução da depressão, os autores concluíram que nenhum dos produtos testados demonstraram efeito redutor da depressão peri-menopausa.…”
Section: Discussionunclassified
“…Embora seja usado como suplemento alimentar nesse país, nunca obteve aprovação para uso médico. Schmidt et al (2021) desenvolveram um estudo clínico randomizado para avaliar o efeito sobre a depressão de mulheres no período da menopausa, onde utilizaram 4 grupos: palacebo; estradiol; raloxifene (fitohormônio da classe das benzofenonas) e o suplemento rimostil (isolflavonas isoladas de Trevo vermelho). Neste estudo para avaliar a ação desses produtos na redução da depressão, os autores concluíram que nenhum dos produtos testados demonstraram efeito redutor da depressão peri-menopausa.…”
Section: Discussionunclassified
“…Yalamanchili et al 75 studied older postmenopausal women (65–77‐year‐old) and found no effect of HRT compared to placebo on GDS ( n = 489). A more contemporaneous but small study ( n = 66) by Schimdt et al 76 in 2021 replicated these findings, finding no beneficial effect in any treatment arm when assessing transdermal E2, raloxifene (a selective oestrogen receptor modulator), phytoestrogen or isoflavone. Cohen et al 73 carried out a study on peri‐ or postmenopausal women with a known diagnosis of depression ( n = 22).…”
Section: Mood and Hrtmentioning
confidence: 92%
“…A study of 62 women with menopause-related depression with MHT randomized to four treatment groups (raloxifene 60 mg/day; a phytoestrogen, Rimostil; transdermal estradiol [TE; 100 μg/day]; or placebo). No improvement in depression was described after the 8-week study for the women in any treatment arm [ 112 ]. The authors concluded “No differences were observed between raloxifene and either TE or placebo in any scale score”.…”
Section: Treatment Of Menopause-associated Depressionmentioning
confidence: 99%